Endocrine disruptor activity of multiple environmental food chain contaminants. Issue 1 (February 2015) - Wielogórska, E.; Elliott, C.T.; Danaher, M.; Connolly, L.
Highlights Many food chain contaminants possess estrogenic hormonal activity. Pyrethroid metabolites express higher estrogenicity than their parent compounds. Parabens and UV filters enhance 17β-estradiol mediated response.